Structural strengthening of a historical building in Rio Branco city-Acre - Amorim, D. C. S.; Oliveira, D. R. C. (Revista ALCONPAT, 2015)
This work presents the use of the technique of structural reinforcement for jacketing applied in the reform of the historical building called "Big House", due to the architectural need to remain as faithful to the original design,justifying the need for increased resilience without substantial increase in the cross section of the pillars. The results obtained by analyzing the reinforcement relative to rectangular columns subjected to bending, shearing and torsional, in accordance with the NBR 6118 (ABNT, 2014), indicated that the studied technique was efficient because all reinforced parts had a greater bearing capacity and met the current requirements without compromising the structural safety of the building’s characteristic architectural. Keywords: historic building; structural strengthening; jacketing.